2021
DOI: 10.3389/fimmu.2021.672449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CpG Depletion of Vector Genome on CD8+ T Cell Responses in AAV Gene Therapy

Abstract: Adeno associated viral (AAV) vectors have emerged as a preferred platform for in vivo gene replacement therapy and represent one of the most promising strategies to treat monogenetic disorders such as hemophilia. However, immune responses to gene transfer have hampered human gene therapy in clinical trials. Over the past decade, it has become clear that innate immune recognition provides signals for the induction of antigen-specific responses against vector or transgene product. In particular, TLR9 recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…This is in contrast to CNS studies showing that AAVrh10 provides higher expression compared to other serotypes 34 , 35 . This might be either due to the fact that a number of capsids are trapped in different cell types such as ependymal cells, or due to the presence of unproductive viral particles which may result also in CD8 toxicity associated to TLR9 activation 38 , 39 . In contrast to expression rates, expression levels of EGFP and Cx32 detected by immunoblot analysis tended to be higher with AAVrh10 compared to AAV9 although there was marked variability between samples from different animals.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to CNS studies showing that AAVrh10 provides higher expression compared to other serotypes 34 , 35 . This might be either due to the fact that a number of capsids are trapped in different cell types such as ependymal cells, or due to the presence of unproductive viral particles which may result also in CD8 toxicity associated to TLR9 activation 38 , 39 . In contrast to expression rates, expression levels of EGFP and Cx32 detected by immunoblot analysis tended to be higher with AAVrh10 compared to AAV9 although there was marked variability between samples from different animals.…”
Section: Discussionmentioning
confidence: 99%
“…The most practiced approach has been removal of CpG rich sequences from the AAV vectors' genome. Animal studies have shown that a reduction of the vectors' CpG motifs blunts CD8 + T cell responses without modifying B cell responses (52). The ITRs are very rich in CpG sequences that cannot be modified so that complete CpG depletion of the AAV vectors' genome may not be feasible (54).…”
Section: Innate Responsesmentioning
confidence: 99%
“…These innate problems associated with rAAV need to be carefully studied in order to improve overall outcomes. The pivotal role of TLR9 activation [ 93 ] as a mediator of both the cellular and humoral immune response needs to be analyzed further, as well as CpG motifs in the vector genome, which can drive the immune responses associated with CD8+ T-cell activation [ 94 ]. The introduction of novel technologies, such as incorporating short DNA oligonucleotides in vector genomes that antagonize TLR9 activation, may be beneficial in reducing TLR9-mediated immune responses and may allow higher doses to be infused in patients [ 95 ].…”
Section: Gene Therapy For Pompe Diseasementioning
confidence: 99%